2022
DOI: 10.3390/e24060760
|View full text |Cite
|
Sign up to set email alerts
|

On the Choice of the Item Response Model for Scaling PISA Data: Model Selection Based on Information Criteria and Quantifying Model Uncertainty

Abstract: In educational large-scale assessment studies such as PISA, item response theory (IRT) models are used to summarize students’ performance on cognitive test items across countries. In this article, the impact of the choice of the IRT model on the distribution parameters of countries (i.e., mean, standard deviation, percentiles) is investigated. Eleven different IRT models are compared using information criteria. Moreover, model uncertainty is quantified by estimating model error, which can be compared with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 114 publications
1
40
0
2
Order By: Relevance
“…The 3PLRH model has been successfully applied to LSA data and often resulted in superior model fit compared to the three-parameter logistic model (3PL; [ 48 ]) that includes a guessing parameter instead of an asymmetry parameter [ 51 , 52 , 53 , 54 ]. In this study, we did not include the 3PL model for two reasons, even though the PISA test includes multiple-choice items.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The 3PLRH model has been successfully applied to LSA data and often resulted in superior model fit compared to the three-parameter logistic model (3PL; [ 48 ]) that includes a guessing parameter instead of an asymmetry parameter [ 51 , 52 , 53 , 54 ]. In this study, we did not include the 3PL model for two reasons, even though the PISA test includes multiple-choice items.…”
Section: Methodsmentioning
confidence: 99%
“…Alternative models might be preferable if the goal is to adjust for guessing effects adequately [ 55 , 57 ]. In a previous study, we demonstrated that the 3PL model did not substantially improve the model fit compared to the 2PL model [ 54 ]. In contrast, the 3PLRH model significantly improved the model fit in terms of information criteria [ 54 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations